CONTEXTUALIZED SCIENCE LEARNING AND STUDENT’S TRANSITION FROM SECONDARY SCHOOL TO UNIVERSITY: THE CASE OF A PUBLIC DAY SECONDARY SCHOOL IN KENYA (Proceedings of the International Conference on Future of Education, 2018)
Day schools do not offer boarding facilities, so students report to school in the morning, have their lessons the whole day, and go back home in the evening. In Kenya, Day school students hardly qualify for University admission, partly because of lack of science learning facilities. This research investigated whether contextualized Science learning at a local jua kali workshop could improve students interest and understanding in STEM related concepts and hence contribute to their transition to University. The investigation employed a case study approach where Form three (Grade 11) students from a Day secondary school experienced a 9-week contextualized science learning that involved a full day interaction with Jua Kali1 artisans. The interaction involved students moving in groups at the workshop, observing the processes and discussing relevant scientific concepts with the artisans. Later in school, the groups were tasked with discussing and sharing their best learnt science concepts with the entire class through presentations. The following year, the same students sat for the Kenya Certificate of Secondary Education (KCSE) examination, a National examination done countrywide at the end of secondary school cycle, and the one that determines student’s transition to University. In Kenyan Education System, a student with grade C+ and above qualifies for University admission, according to Joint Admission Board (JAB), the body that determines University entrance grades. Based on minimum grade of C+, the school performance improved significantly from 47.48% to 68.4% (X2=7.110’P=0. 008.From this research, Jua kali workshops could act as a sustainable science learning laboratory for disadvantaged schools with the artisans teaching in collaboration with regular teachers. Thus Contextualized learning using student’s local environment could help improve Day school students transition to University.
Keywords: Jua Kali; contextualize; curricula